The use of the »Brainwashing« Theory by the Anti-cult Movement in the United States of America, pre-1996 - Elizabeth Aileen Young (Zeitschrift für Junge Religionswissenschaft)
The »problem« of cults, or new religious movements (NRMs), has been a polarising issue for centuries. The massive culture shift that took place in the 1960s saw the »problem« of cults coupled with the emergent »brainwashing« theory. This article sheds light on exactly what this so-called brainwashing theory is, providing ample evidence for its illegitimacy as an explanation as to why people join new religious movements. Tracing the history of the theory back to its inception by secret arms of both the US government and Nazi Germany, the article provides evidence for the falsity of the theory. The two concepts – brainwashing and cults – were brought together by the »anti-cult movement« (ACM) in the United States in the 1960s. After detailing these initial concepts, the article moves on to the history and development of the ACM, which accused many NRMs of using »cultic brainwashing« techniques in order to gain converts. In order to rid »victims« of these beliefs, the ACM often used violent and dangerous »deprogramming« techniques leading to the eventual downfall of the movement in 1996. Moreover, the author invites the reader to see the parallels between the actions of the alleged »cults« and those of the ACM, highlighting that the two are not so different.